Islamic Ecopedagogy Curriculum Model in Muhammadiyah Schools - Nurokhman Nurokhman; Riza Awal Novanto; Moncef Ben Abdeljelil; Sayyaf Muhammad Robbani; Herny Putriana (Universitas Muhammadiyah Mataram, 2026)
Environmental degradation and the limited integration of ecological values in Islamic school curricula indicate a gap between Islamic environmental ethics and educational practice. While previous studies have discussed environmental awareness programs in Islamic education, few have formulated a comprehensive curriculum model that systematically integrates Islamic theological principles, ecological values, and pedagogical practices. This study aims to examine and formulate an Islamic ecopedagogy curriculum model implemented in a Muhammadiyah primary school to strengthen students’ ecological awareness grounded in Islamic values. The research employed a qualitative case study design conducted at SD Muhammadiyah Slawi. Data were collected through semi-structured interviews with the principal, vice principal for curriculum affairs, six teachers, and eight students, supported by non-participant observations and document analysis of curriculum plans, school regulations, and environmental programs. Interview and observation guides were used as research instruments to ensure systematic data collection. Data were analyzed thematically using NVivo 12 through open coding, category development, and theme construction. The findings indicate that Islamic ecopedagogy functions as an integrated educational ecosystem consisting of five interrelated components: Islamic ecological values (tauhid and khalifah), curriculum integration across subjects, habituation-based environmental practices, digital ecological literacy, and environmentally friendly school culture. This study contributes a conceptual Islamic ecopedagogy curriculum model that extends previous Islamic environmental education approaches by positioning ecological values as a structural orientation of curriculum, pedagogy, and institutional culture rather than as a supplementary program. The model provides a theoretical framework for integrating Islamic ethical principles with ecopedagogical learning and offers practical guidance for developing sustainable environmental education in Muhammadiyah and other Islamic educational institutions. Environmental degradation and the limited integration of ecological values in Islamic education highlight the need for a curriculum that connects religious teachings with environmental responsibility. This study aims to examine and formulate an Islamic ecopedagogy curriculum model developed in a Muhammadiyah primary school to foster ecological awareness grounded in Islamic values. This research employed a qualitative case study conducted at SD Muhammadiyah Slawi. Data were collected through in-depth interviews with the principal, vice principal for curriculum affairs, teachers, and students, supported by observations and document analysis. The data were analyzed thematically using NVivo to identify patterns related to value integration, curriculum practices, school culture, and digital learning. The findings reveal that Islamic ecopedagogy operates as an integrated educational ecosystem encompassing the internalization of Islamic values, daily habituation, cross-curricular learning, environmentally friendly school culture, and digital innovation. Concepts such as tauhid, khalifah fil ardh, and cleanliness as part of faith are embedded in learning activities and school routines. Teachers act as facilitators and role models, while digital media and environmental programs strengthen student engagement and behavioural change. This study proposes a practical, culturally grounded, and sustainable Islamic ecopedagogy curriculum model that emphasises value internalisation, participatory learning, and institutional support. The findings imply that environmental education in Islamic schools should be positioned as a holistic character-forming process rather than a separate subject, and that the model may serve as a reference for developing Islamic-based environmental education in Muhammadiyah and other Islamic educational institutions.